43 Fachwörterbuchartikel in Grammatik: Syntax - Rink, Christian (2018)

Bilinguale Fachlexikographie – Konzeption eines Fachwörterbuches zur antiken Baukunst Chinas - Rink, Christian (Lexicographica, 2017)
Ancient Chinese architecture has amongst other outstanding properties because of its complex structure a broad and confusing field of terminology, which includes a variety of terms that do not exist in German, or in other languages as well. Therefore, it is a necessity for a deeper understanding of the traditional architecture of ancient China to create a bilingual specialized dictionary from Chinese to German. This dictionary must comply with the knowledge of lexicographical research. After the description of some important basics of the Chinese lexicography and the analysis of some mono- and bilingual architectural dictionaries of other languages, this specialized dictionary will be based on Chinese and Western lexicographical standards including dictionary typology, functions and structures, such as access and textual structures, and macro, micro and mediostructures in addition to types of indices, user purposes, content of lemmata etc.
Keywords: zweisprachige Lexikographie; Fachlexikographie; chinesische Lexikographie; chinesische Architekturterminologie; Wörterbuchkonzeption

Multi-level analysis as a systematic Approach to evaluating the quality of AI-generated dictionary entries - Evert, Stephanie; Ganslmayer, Christine; Rink, Christian (Proceedings of the XXI EURALEX International Congress, 2024)
In this paper, we report on our development of a multi-level analysis framework that allows us to assess AI-generated lexicographic texts on both a quantitative and qualitative level and compare them with human-written texts. We approach this problem through a systematic and fine-grained evaluation, using dictionary articles created by human subjects with the help of ChatGPT as an example. The levels of our framework concern the assessment of individual entries, a comparison with existing dictionary entries written by experts, an analysis of the writing experiment, and the discussion of AI-specific aspects. For the first level, we propose an elaborate evaluation grid that enables a fine-grained comparison of dictionary entries. While this grid has been developed for a specific writing experiment, it can be adapted by metalexicographical experts for the evaluation of all kinds of dictionary entries and all kinds of dictionary information categories.<br
Keywords: conversational AI; generated lexicographical data; dictionary criticism; evaluation methodology; semantic analysis; standard dictionaries

Towards a comprehensive method for evaluating and utilizing AI-generated bilingual lexicographic data in language learning using the example of Chinese as a foreign language - Rink, Christian; Ganslmayer, Christine; Evert, Stephanie (Asian Lexicography - Merging cutting-edge and established approaches, 2024)
In this paper, we take an analytical and a practical approach to the topic of AI-generated lexicographical data. In the context of a language-learning environment, we want to take a closer look at the quality of bilingual lexicographical data (Chinese-German) produced by generative large language models (LLMs). Our aim is to create a scientifically supported and comprehensive method that includes effective prompting strategies, an objective evaluation of the generated lexicographical data, and learner strategies for the use of conversational AI. The focus of our paper will be on the evaluation method, for which we use a multi-level analysis based on lexicographical standards, in comparison with existing lexicographical resources made by experts, the consideration of the findings of a didactical experiment, as well as a discussion about AI specific questions, and on the proposal of a didactical concept, which introduces a reasonable use of conversational AI chatbots in a language-learning environment. The results of this study are expected to give further insight into the functionality of generative LLMs in lexicographical settings, to provide a critical framework for the evaluation of AI-generated lexicographical data, and offer perspectives on how it can be used as a valuable lexicographical tool in language-learning.<br
Keywords: lexicographical data generated by conversational AI; evaluation methods; bilingual lexicography; Chinese as a foreign language; didactical concepts